PENGARUH USAHA EKONOMI DESA-SIMPAN PINJAM (UED-SP) TERHADAP PENINGKATAN PENDAPATAN MASYARAKAT DI DESA KUALU KECAMATAN TAMBANG KABUPATEN KAMPAR - Nur Aisyah Aisyah; Gusnardi '; RM.Riadi Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This  study was conducted to test the Ruler Ekonomic Business Influence-Savings And Loans (UED-SP) Against Public Revenue Improvement In the village Kualu Mining District of Kampar regency. Population in this research are 221 beneficiaries who borrow additional funds or venture capital. Of these 68 people taken sampled and composed of different sectors Data analysis technique using quantitative descriptive method. The result showed that the Rular Economy-Savings and Loans (UED-SP) Business Development influential Socienty Against Increased Revenue In the village Kualu Mining District of Kampar regency. Great contribution of independent variable to improve household incomes in addressed by the numbers (R square) of 10,4%. This figure gives the sense that the independent variables are UED-SP are used in the regression equation was able to explain the increase in people’s income by 10,4% the remaining 89,6% is influenced by othet  factors not examined in this study. Furthermore, the results obtained from the regression equation is Y= 395,307,725 + 0,171, thus the analysis of the effect is positive. Great influence in the amount of 0,171. The next test of significance is 0.007 significantly smaller than that formed the basis of 0,05. To see the close relationship or correlation between UED-SP (X) to Income (Y) Poeple in the village kualu Mining District of Kampar district in numbers indicated by the correlation coefficient (R) of 0,323 or 32,3% Keywords: Economic Enterpries-Village Savings and Loans (UED-SP), Income Communities